ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT PERBANKAN DI INDONESIA PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010 - 2013 - Irnila Intan Permata Dewi, 11.05.52.0118; Aini, Nur (Students Journal of Accounting and Banking, 2015)
This study aims to analyze and examine the factors that affect bank credit in Indonesia. The population in this study is a banking company that is listed on the Indonesia Stock Exchange during the observation period 2010-2013. The sampling technique using purposive sampling method. Hypothesis testing using multiple linear regression analysis with the Statistical Product and Service Solutions. Hypothesis testing results prove that the Third Party Fund (DPK) significant positive effect on credit, while the Capital Adequacy Ratio (CAR) and non-performing loan (NPL) significant negative effect on credit. Statutory Reserves (GWM) is not a significant positivefor credit.Keywords: Third Party Fund, Capital Adequacy Ratio, Non-Performing Loan, Statutory Reserves, Credit